Synthesis and characterization of Jatropha (Jatropha curcas L.) oil-based polyurethane wood adhesive - Aung, Min Min; Yaakob, Zahira; Kamarudin, Siti Kartom; Abdullah, Luqman Chuah (Elsevier, 2014)
Vegetable oil-based adhesives emerged as an environmentally friendly substitute for petrochemical-based materials. Palm oil-based adhesives have been studied extensively and the poor performance it is probably due to the high content of saturated fatty acids. However, vegetable oil-based adhesives which have high content of unsaturated fatty acid could be used to make commercial adhesives. Jatropha oil is non-edible oil and it has 78.5% unsaturated fatty acids. In this study, jatropha oil-based polyurethane adhesive was developed as wood adhesives and compared with palm oil-based adhesive. Polyol was prepared by hydroxylation and alcoholysis to further react with isocyanate to form adhesives resin. Polyol and polyurethane analysis was performed using spectroscopic techniques, such as FTIR and 1H NMR. Shear strength tests with jatropha oil-based adhesive of solid wood and plywood exhibited better results compared with palm oil-based adhesives. The overall resistance of the chemical properties of jatropha oil-based polyurethane adhesives in response to hot water, acid, and alkali was superior compared to palm oil-based adhesives.